Dissolution of Quartz, Albite, and Orthoclase in H2O-Saturated Haplogranitic Melt at 800°C and 200MPa: Diffusive Transport Properties of Granitic Melts at Crustal Anatectic Conditions - Acosta-vigil A.; London D.; Morgan G.B.; Dewers T.A. (My University, 2006)
We have conducted experiments on dissolution of quartz, albite, orthoclase, and corundum into H2O-saturated haplogranite melt at 800°C and 200?MPa over a duration of 120–1488?h with the aim of ascertaining the diffusive transport properties of granitic melts at crustal anatectic temperatures. Cylinders of anhydrous starting glass and a single mineral phase (quartz or feldspar) were juxtaposed along flat and polished surfaces inside gold or platinum capsules with ≈10 wt % added H2O. Concentration profiles in glass (quenched melt) perpendicular to the mineral–glass interfaces and comparison with relevant phase diagrams suggest that melts at the interface are saturated in the dissolving phases after 384?h, and with longer durations the concentration profiles are controlled only by diffusion of components in the melt. The evolution of the concentration profiles with time indicates that uncoupled diffusion in the melt takes place along the following four linearly independent directions in oxide composition space: SiO2, Na2O, and K2O axes (Si-, Na-, and K-eigenvectors, respectively), and a direction between the Al2O3, Na2O, and K2O axes (Al-eigenvector), such that the Al/Na molar ratio is equal to that of the bulk melt and the Al/(Na + K) molar ratio is equal to the equilibrium ASI (= mol. Al2O3/[Na2O + K2O]) of the melt. Experiments in which a glass cylinder was sandwiched between two mineral cylinders—quartz and albite, quartz and K-feldspar, or albite and corundum—tested the validity of the inferred directions of uncoupled diffusion and explored long-range chemical communication in the melt via chemical potential gradients. The application of available solutions to the diffusion equations for the experimental quartz and feldspar dissolution data provides diffusivities along the directions of the Si-eigenvector and Al-eigenvector of ≈(2·0–2·8) ? 10?15 m2/s and ≈(0·6–2·4) ? 10?14 m2/s, respectively. Minimum diffusivities of alkalis [≈(3–9) ? 10?11 m2/s] are orders of magnitude greater than the tetrahedral components of the melt. The information provided here determines the rate at which crustal anatexis can occur when sufficient heat is supplied and diffusion is the only mass transport (mixing) process in the melt. The calculated diffusivities imply that a quartzo-feldspathic source rock with initial grain size of 2–3?mm undergoing hydrostatic, H2O-saturated melting at 800°C (infinite heat supply) could produce 20–30 vol. % of homogeneous melt in less than 1–10 years. Slower diffusion in H2O-undersaturated melts will increase this time frame.